2022
DOI: 10.3390/insects13100882
|View full text |Cite
|
Sign up to set email alerts
|

The Fallacy of Year-Round Breeding in Polyphagous Tropical Fruit Flies (Diptera: Tephritidae): Evidence for a Seasonal Reproductive Arrestment in Bactrocera Species

Abstract: The genus Bactrocera (Diptera: Tephritidae) is endemic to the monsoonal rainforests of South-east Asia and the western Pacific where the larvae breed in ripe, fleshy fruits. While most Bactrocera remain rainforest restricted, species such as Bactrocera dorsalis, Bactrocera zonata and Bactrocera tryoni are internationally significant pests of horticulture, being both highly invasive and highly polyphagous. Almost universally in the literature it is assumed that Bactrocera breed continuously if temperature and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…In Senegal, the latter technique could be deployed during the off-dry season (from February to May) when fly population is low and concentrated in preferred habitats (eg, areas with a dense overhead canopy and high relative humidity). This could prevent population outbreaks at the time of mango fruiting, provided that low temperatures (Meats A & Fay 1976) or reproductive arrestment (Clarke et al 2022) do not reduce fly interactions and in the end spore transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In Senegal, the latter technique could be deployed during the off-dry season (from February to May) when fly population is low and concentrated in preferred habitats (eg, areas with a dense overhead canopy and high relative humidity). This could prevent population outbreaks at the time of mango fruiting, provided that low temperatures (Meats A & Fay 1976) or reproductive arrestment (Clarke et al 2022) do not reduce fly interactions and in the end spore transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Female fruit flies lay eggs deep inside fruits and vegetables, leading to mechanical damage, microorganism infections, and direct feeding by the larvae after hatching, thus leading to dropping and rotten fruit 5,6 . Additionally, females can reproduce continuously under unrestricted temperature and host conditions 7 . Such characteristics have made it very difficult to control fruit flies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Clarke et al. ( 4 ) suggested that Bactrocera species undergo a reproductive arrest in the unfavourable season when host plants are unavailable or scarce. This differential seasonal investment in reproduction or survival that appears to be linked to host availability could be associated with a change in nutrient availability, or nutrient regulation, between seasons.…”
Section: Introductionmentioning
confidence: 99%
“…In climatic regions where the year is usually characterised by favourable and unfavourable seasons (e.g., hot and cold or dry and wet), organisms have evolved strategies to cope with fluctuating environments and prioritise investment in some life-history traits over others, depending on the time of the year (1). In tropical and sub-tropical environments for example, where temperatures never drop to levels that may prompt diapause, insects shift their relative investment in reproduction versus survival as the seasons change (2)(3)(4). In such environments, the factor triggering this shift appears to be host plant availability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation